Regulating Contingency Fees: A Consumer Welfare Perspective - Semple, Noel (2019)
How can we preserve and extend what's good about contingency fees, while minimizing the bad and the ugly? In order to identify the regulatory tools best suited to this challenging task, this Chapter proposes a consumer welfare analysis. The consumers of contingency fee legal services are the individual clients, and the members of classes, represented by law firms working on this basis. These consumers, like other consumers, have interests in:(i) quality, (ii) price, (iii) fairness, and (iv) choice. Part 2 of this Chapter will analyze these four sets of consumer interests, all of which are affected by the regulation of contingent fees. Part 3 scrutinizes various regulatory approaches to contingency fees against the consumer welfare criterion. I argue that heavy-handed interventions, such as fee caps and retrospective price review, can do as much harm as good for consumers. "Light touch" alternatives such as disclosure and standardized contracts, and fostering the "invisible hand" of the market, are preferable approaches for a regulators interested in maximizing consumer welfare.
Keywords: Noel Semple